Melatonin modulates daytime‐dependent synaptic plasticity and learning efficiency. Issue 3 (14th February 2019) - Jilg, Antje; Bechstein, Philipp; Saade, Anastasia; Dick, Moritz; Li, Tian Xiao; Tosini, Gianluca; Rami, Abdelhaq; Zemmar, Ajmal; Stehle, Jörg H.
Abstract: Mechanisms of hippocampus‐related memory formation are time‐of‐day‐dependent. While the circadian system and clock genes are related to timing of hippocampal mnemonic processes (acquisition, consolidation, and retrieval of long‐term memory [LTM]) and long‐term potentiation (LTP), little is known about temporal gating mechanisms. Here, the role of the neurohormone melatonin as a circadian time cue for hippocampal signaling and memory formation was investigated in C3H/He wildtype (WT) and melatonin receptor‐knockout ( MT 1 / 2 - / - ) mice. Immunohistochemical and immunoblot analyses revealed the presence of melatonin receptors on mouse hippocampal neurons. Temporal patterns of time‐of‐day‐dependent clock gene protein levels were profoundly altered in MT 1 / 2 - / - mice compared to WT animals. On the behavioral level, WT mice displayed better spatial learning efficiency during daytime as compared to nighttime. In contrast, high error scores were observed in MT 1 / 2 - / - mice during both, daytime and nighttime acquisition. Day‐night difference in LTP, as observed in WT mice, was absent in MT 1 / 2 - / - mice and in WT animals, in which the sympathetic innervation of the pineal gland was surgically removed to erase rhythmic melatonin synthesis. In addition, treatment of melatonin‐deficient C57BL/6 mice with melatonin at nighttime significantly improved their working memory performance at daytime. These results illustrate that melatonin shapes time‐of‐day‐dependent learning efficiency in parallel to consolidating expression patterns of clock genes in the mouse hippocampus. Our data suggest that melatonin imprints a time cue on mouse hippocampal signaling and gene expression to foster better learning during daytime.